Ocorrência e suscetibilidade in vitro a terbinafina, ciclopirox, cetoconazol e itraconazol, com ênfase na combinação entre as drogas antifúngicas de agentes de onicomicose no Estado do Espírito Santo - Hoffmann, Adrielle (2011)
The onychomycosis, fungal nail infections, are caused by filamentous fungi dermatophytes and non-dermatophytes and yeasts and represent the most difficult superficial mycosis to be diagnosed and treated. Treatment involves use of topical and/or oral antifungal drugs, as well as removal of the nail. The use of topical agents concomitant to systemic therapy leads to better clinical and mycological results. The efficacy of combination therapy may be associated with a complementary action between the drugs, involving different levels of nail penetration and, depending on the antifungal, different targets of action in the fungal cell. The purpose of this study was to establish the occurrence of filamentous fungi in the etiology of onychomycosis and in vitro susceptibility to the drugs terbinafine, ciclopirox olamine, ketoconazole and itraconazole, according to document M38-A2 (2008) CLSI. It was also evaluated the combination among these antifungal drugs by calculating the fractional inhibitory concentration index (FICI). Our results showed that the prevalence of onychomycosis in the period from January 2009 to April 2011, in Vitoria, ES, Brazil, was 50% among the dermatomycosis cases. Most of the isolates (77%) were obtained from female patients and toenails were the local with greater involvement for both sexes. The fingernails were more affected by yeast and toenails, by filamentous fungi. In general, the genera of filamentous fungi more prevalent in the etiology of onychomycosis was Trichophyton spp (21.7%), Fusarium spp. (11.2%) and Scytalidium spp. (8.4%). For filamentous fungi, the in vitro susceptibility testing showed that dermatophytes were more susceptible than non-dermatophytes isolates. Among non-dermatophytes, Fusarium spp. was less inhibited than Scytalidium spp., which in turn, was less inhibited than the dermatophyte Trichophyton spp. Among the combinations tested, there was no antagonistic effect and,, with exception of ketoconazole and itraconazole, those ones showed synergistic effect for isolates. The best results were presented for combinations involving itraconazole and terbinafine. The drug combination with greater synergistic effect was observed for genus Scytalidium spp. being that the combination itraconazole and terbinafine presented also the best results for this genus